The impact of institutional ownership on corporate operating performance - Cornett, Marcia Millon; Marcus, Alan J.; Saunders, Anthony; Tehranian, Hassan (Journal of Banking & Finance, 2007)
This paper examines the relation between institutional investor involvement in and the operating performance of large firms. We find a significant relation between a firm’s operating cash flow returns and both the percent of institutional stock ownership and the number of institutional stockholders. However, this relation is found only for a subset of institutional investors: those less likely to have a business relationship with the firm. These results suggest that institutional investors with potential business relations with the firms in which they invest are compromised as monitors of the firm.